Analysis of the Role of Keeper as a Risk Factor for Infection of Gastrointestinal Nematodes in Sumatran Orangutan in the Re-introduction Station of Jantho - Ali Murtala; T. Reza Ferasyi; Erdiansyah Rahmi (Universitas Syiah Kuala, 2014)
This study was aimed to identify the role of keeper as a risk factor for the infection of gastrointestinal nematodes on orangutans in Jantho Re-introduction Station. This study was conducted using a census method. A number of 8 orangutan’s keepers were involved as respondent. The data was collected by interview using a structural questionnaire. In addition, feces of 6 orangutans caged in this location were taken as sample. The feces sample was then examined for gastrointestinal nematodes using native and centrifugation methods in Parasitology Laboratory, Veterinary Medicine Faculty, Syiah Kuala University. The data obtained from this study were analyzed descriptively. The results of study by questionnaire showed that a possible potential risk factor for the infection of gastrointestinal nematode to orangutans in Jantho Re-introduction Station is the keeper avoids using gloves when supplying food to the animals. Then, the result of laboratory examination showed that it was confirmed that the feces of orangutans infected with gastrointestinal nematodes, which the prevalence of 16.5% for infection by Strongiloides sp. In conclusion, orangutans caged in Jantho Re-introduction Station are in a low infection of gastrointestinal nematodes of Strongiloides sp., and the keeper shows a good behavior to prevent gastrointestinal nematodes infection to orangutan.Key words: keeper, Sumateran orangutan, Pongo abelii, Strongyloides sp.